Involving youth with disabilities in the development and evaluation of a new advocacy training: Project TEAM. (April 2013) - Kramer, Jessica; Barth, Yishai; Curtis, Katie; Livingston, Kit; O'Neil, Madeline; Smith, Zach; Vallier, Samantha; Wolfe, Ashley
<x xml:space="preserve">Abstract</x> Purpose: This paper describes a participatory research process in which six youth with disabilities (Youth Panel) participated in the development and evaluation of a manualized advocacy training, Project TEAM (Teens making Environment and Activity Modifications). Project TEAM teaches youth with disabilities how to identify environmental barriers, generate solutions, and request accommodations. Method: The Youth Panel conducted their evaluation after the university researcher implemented Project TEAM with three groups of trainees. The Youth Panel designed and administered a survey and focus group to evaluate enjoyment and usefulness of Project TEAM with support from an advocate/researcher. Members of the Youth Panel analyzed survey response frequencies. The advocate/researcher conducted a content analysis of the open-ended responses. Results: Sixteen of 21 Project TEAM trainees participated in the evaluation. The evaluation results suggest that the trainees found the interactive and individualized aspects of the Project TEAM most enjoyable and useful. Some instructional materials were difficult for trainees with cognitive disabilities to understand. Conclusions: The Youth Panel's involvement in the development of Project TEAM may explain the relatively positive experiences reported by trainees. Project TEAM should continue to provide trainees with the opportunity to apply concepts in real-life situations. Project TEAM requires revisions to ensure it is enjoyable and useful for youth with a variety of disabilities.